MODELLING SUPPLY CHAIN MANAGEMENT ANTECEDENTS WITH JUST IN TIME PERFORMANCE AND EFFECTIVE DISASTER RESPONSE MEDIATED BY READINESS - Maimunah Omar (Tesis, 2017)
Supply chain management antecedents are very important with regards to ensuring the success of any disaster response mission in Malaysia. Therefore the aim of this study is to determine the best SCM model to achieve JIT in order to ensure the effectiveness of disaster responses.